2013
DOI: 10.3892/br.2013.73
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the urokinase gene 3′-UTR T/C polymorphism and susceptibility to urolithiasis

Abstract: Abstract. Urokinase is involved in the processes of initiating urinary stones. Several published case-control studies have examined the relationship of urokinase gene 3'-untranslated region (3'-UTR) T/C polymorphism and urolithiasis, but yielded inconsistent findings. In this study, a comprehensive meta-analysis was conducted by pooling relevant studies to obtain reliable conclusions. Studies focusing on the association between urokinase gene 3'-UTR T/C polymorphism and urolithiasis were retrieved through PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Urolithiasis, as a complex and multifactorial disease, is one of the most prevalent disorders in the urological system with increasing incidence. Approximately 5% of females and 12% of males are likely to develop urolithiasis during their lifetime [ 30 ]. A growing body of evidence shows that organic substances, in addition to inorganic substances, may significantly influence the development of urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis, as a complex and multifactorial disease, is one of the most prevalent disorders in the urological system with increasing incidence. Approximately 5% of females and 12% of males are likely to develop urolithiasis during their lifetime [ 30 ]. A growing body of evidence shows that organic substances, in addition to inorganic substances, may significantly influence the development of urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have also identified genetic polymorphisms associated with kidney stone disease in the following genes: HIPK2 (the protein product of which is thought to have a role in renal tubule epithelial cell apoptosis and renal fibrosis 174 ; SPP1 which encodes an inhibitor of stone formation [175][176][177] ; MGP, the protein product of which inhibits hydroxyapatite nucleation and formation of calcium oxalate monohydrate 178,179 ; and a variant in the 3' UTR of the urokinase gene, which encodes a protein that degrades the organic matrix of kidney stones 180 . Further studies are required to elucidate the role of these genetic polymorphisms in kidney stone pathogenesis.…”
Section: [H2] Case-control Studiesmentioning
confidence: 99%
“…Risk factors related to kidney stones are different among different population groups and environmental factors have a key role in their pathogenesis [5]. Research on urological patients has shown that the incidence of kidney stones can be associated with sex, race, geographic region, occupation, hot climate, positive family history, unhealthy diet (excessive intake of caffeine, salt, dairy products, animal proteins and fat) [6], smoking, alcohol consumption, physical activity, obesity, low fluid intake, dehydration [2] socioeconomic status, education [5], water quality [7], high intake of vitamins D and C [8], genetic background [9] and comorbid metabolic disorders (diabetes mellitus, hypertension, chronic kidney disease, and cardiovascular disease) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologically, about 5% of women and 12% of men experience kidney stones during their lives [9]. Basiri et al which conducted a study on the prevalence of urinary stones among 24 provinces of Iran, reported an average age of 41.5 years for the patients [7].…”
Section: Introductionmentioning
confidence: 99%